Fuel subsidy reform and the social contract in Nigeria: A micro-economic analysis. (September 2021) - McCulloch, Neil; Moerenhout, Tom; Yang, Joonseok
Abstract: Fuel subsidies in Nigeria are enormous – around USD 3.9 billion – almost double the health budget. Such subsidies come at great cost: the opportunity costs of such spending on other development objectives are large; the distribution of resources to the state governments is reduced; the vast majority of the subsidy goes to better off Nigerians; and cheaper petrol encourages greater pollution, congestion and climate change. Despite this, most Nigerians oppose the reduction of subsidies. We draw on a new nationally representative household survey that asked Nigerian men and women about their knowledge and attitudes towards subsidies. We construct and test a set of hypotheses about the factors associated with support for subsidy reform. We find that those who pay more or who experience less availability of fuel tend to support reform more. On the other hand, people who believe the Government is corrupt or lacks the capacity to implement compensation programs appear strongly opposed to reform. Finally, being religious and the delivery of reasonable national and local services also improves the acceptance of reform. These results support the idea that building a social contract is key to reform success. Highlights: Results from a new household survey in Nigeria (N = 16, 000) on subsidy reforms. Economic factors and service delivery improve acceptance of gasoline subsidy reform. Beliefs about corruption are strongly correlated with opposition to subsidy reform. Beliefs about incompetence to use subsidy savings also correlate with opposition. Results support the idea that building a social contract is key to reform success.